Catalyst coating of 3D printed structures via electrochemical deposition: Case of the transition metal chalcogenide MoSx for hydrogen evolution reaction. (September 2020) - Iffelsberger, Christian; Ng, Siowwoon; Pumera, Martin
Highlights: 3D printed electrodes based on graphene are fabricated. MoS2 is electrodeposited on their surface. Electrochemical activity is studied by scanning electrochemical microscopy with high resolution. Abstract: Fused filament modeling (FFM) is the most common and simplest type of 3D printing. Conductive composite filaments have become widely used for 3D printing of electrodes and electrochemical devices for sensing, energy storage and energy conversion applications. To enhance the electrochemical performance of the 3D printed parts, post printing procedures are applied. These for example consist of atomic layer deposition, which is high-end equipment demanding. We offer simple, scalable and room temperature method of coating the 3D-printed electrode surfaces via desired catalyst via electrodeposition. We show the electrodeposition of MoSx which is highly catalytic to hydrogen evolution reaction as a case study of such thin film electrodeposition. The applicability of the self-standing 3D printed nanostructure for energy conversion purposes is demonstrated. Valuable information about the heterogeneity of the activity of the catalyst is provided by the scanning electrochemical microscopy (SECM). Electrodeposition is a universal technique which allows turning the surface of 3D objects into catalysts. Graphical abstract: Image, graphical abstract